2020
DOI: 10.1371/journal.pone.0236415
|View full text |Cite
|
Sign up to set email alerts
|

Use of telehealth for facilitating the diagnostic assessment of Autism Spectrum Disorder (ASD): A scoping review

Abstract: There is a significant delay between seeking help and a confirmed diagnosis of Autism Spectrum Disorder (ASD). This delay can lead to poor outcomes for both the families and individuals. Telehealth potentially offers a way of improving the diagnostic pathway for ASD. We conducted a scoping review examining which telehealth approaches are used in the diagnosis and assessment of ASD in children and adults, whether they are feasible and acceptable, and how they compare with face-to-face diagnosis and assessment m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 57 publications
4
67
0
3
Order By: Relevance
“…There have been increased interest and a growing literature on the feasibility of using either Real-Time or Store-and-Forward telemedicine for ASD diagnostic assessments and interventions. 44 For example, Smith et al 54 compared the use of Naturalistic Observation Diagnostic Assessment with the in-person evaluation and found high rates of both diagnostic sensitivity and specificity (84.5% and 94.4%, respectively). Using a real-time method, Reese et al 55 found improved access to diagnostic services and high agreement between face-to-face and videoconferencing for the diagnostic assessment of children with suspected ASD.…”
Section: Approaches Toward Equitable Carementioning
confidence: 99%
See 2 more Smart Citations
“…There have been increased interest and a growing literature on the feasibility of using either Real-Time or Store-and-Forward telemedicine for ASD diagnostic assessments and interventions. 44 For example, Smith et al 54 compared the use of Naturalistic Observation Diagnostic Assessment with the in-person evaluation and found high rates of both diagnostic sensitivity and specificity (84.5% and 94.4%, respectively). Using a real-time method, Reese et al 55 found improved access to diagnostic services and high agreement between face-to-face and videoconferencing for the diagnostic assessment of children with suspected ASD.…”
Section: Approaches Toward Equitable Carementioning
confidence: 99%
“…Using a real-time method, Reese et al 55 found improved access to diagnostic services and high agreement between face-to-face and videoconferencing for the diagnostic assessment of children with suspected ASD. Overall, the use of telehealth in the field of ASD has been shown to be an effective, acceptable, and usable modality for both clinical evaluation and behavioral intervention 44 and represents a scalable alternative to traditional methods. Telehealth offers advantages for increasing access to diagnosis and care, expediting the diagnostic process and receipt of early intervention services, decreasing provider and patient costs, and increasing provider coverage area.…”
Section: Approaches Toward Equitable Carementioning
confidence: 99%
See 1 more Smart Citation
“…The onset of the COVID-19 pandemic, including suspension of in-person appointments and ongoing social distancing requirements in clinic settings, hastened tele-assessment uptake (Berger et al, 2021;Jang et al, 2021;Wagner et al, 2020). Alfuraydan (2020) reviewed 10 studies investigating ASD tele-assessment from 2000 to 2019. Findings suggest that there is potential for telehealth models to improve access to assessment and diagnosis of ASD, especially in those individuals with clear symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Although that study was not powered to show discriminative ability between the face to face and the remote version of Module 4 of the ADOS the study adopted, the authors claimed that “an autism assessment can be administered remotely with high levels of reliability using ADOS-2” [ 17 ]. A different scoping review in the use of telehealth for facilitating the diagnostic assessment of Autism identified 10 studies [ 18 ] and suggested that for certain presentations, remote assessment methods might be as reliable as face to face consultations when making a diagnosis [ 18 ]. This claim however cannot be extended at least to adults, since the only adult study the authors included was the Schutte et al [ 19 ] study.…”
Section: Introductionmentioning
confidence: 99%